A S Geyser, teologiese dosent 1946-1961 - Aarde, Andries van (Hervormde teologiese studies, 1992)
A S Geyser, lecturer in theology 1946-1961 In this article the academic role of Professor A S Geyser is briefly discussed. He lectured in New Testament Studies and Practical Theology at the University of Pretoria from 1946. He resigned in 1961, after a period of strife. His publications show a consistence in exegetical approach and theological description. His historical-critical investigation was aimed beyond the New Testament into the pretexts which evidenced the commencement of the universal apostolate at Antioch. Inferred from his exegetical results he propounded the unity of the church as an imperative for today. However, against the background of the South African political history from 1948 to 1961, the political and ecumenical implications of Geyser’s theological convictions were not acceptable to the Nederduitsch Hervormde Kerk.